A CASE STUDY OF POLYHYDROMNIOS - Rani. S, Vidya; Ravinder, Ch. (International Journal of Ayurveda and Pharma Research, 2015)
The fetus develops inside of a sac that is surrounded by a membrane called the amnion. The sac contains amniotic fluid, which surrounds the developing fetus and protects the fetus from injuries. Polyhydramnios (Garbhodhaka vriddhi) is a condition that occurs when there is too much accumulation of liquor amnii. The exact cause is unknown, but it may be the result of deficient absorption & excessive production of liquor amnii. Liquor amnii exceeds 2000ml, AFI is more than 25cm. It probably occurs in 1 in 1000 pregnancies. Susrutha described one characteristic of Garbha vriddhi as Jataraabhi vriddhi (increase in size of the abdomen). That increase may be due to variation in Sankya (multiple pregnancies), size (big baby) or fluid (hydromnios) of Garbha. Bhavamisra adds further that labour is much difficult. Abnormal amniotic fluid volume can be associated with increased maternal risk as well as perinatal morbidity and mortality. Successful management depends upon appropriate diagnostic evaluation. Prolongation of the pregnancy for further fetal maturation may be achieved with timely therapeutics. This article describes the case report of a 23 year old woman who is a primi complicated by polyhydramnios, which developed between 26 & 28 weeks of pregnancy. Ayurveda being an eternal medicine many treatments are described by Acharyas. The background of the study is Jalodara chikitsa. It is concluded that Ayurveda is useful for treating polyhydramnios, as an alternative to Diuretics, Indomethacin & amniocentesis.